2008
DOI: 10.1007/s11300-008-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

The Banking Network as a Transmission Channel of Migrant Remittances: The Case of Greek and Italian Banks in Albania

Abstract: Albania, Bank, Greece, Italy, Migration, Remittances, F22, F24, G21,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Remittances present a continuous growth with the exception of 3 years, 1997, 1999 and 2005 (see Karafolas and Sariannidis 2009). Remittances result for the most part through the parallel market during the period 1994-2007 despite the bigger growth of remittances through the official market, especially after the pyramid chaos in 1997.…”
Section: Remittances Of Albanian Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remittances present a continuous growth with the exception of 3 years, 1997, 1999 and 2005 (see Karafolas and Sariannidis 2009). Remittances result for the most part through the parallel market during the period 1994-2007 despite the bigger growth of remittances through the official market, especially after the pyramid chaos in 1997.…”
Section: Remittances Of Albanian Immigrantsmentioning
confidence: 99%
“…Nevertheless, there are still few studies focusing on this aspect. Karafolas and Sariannidis (2009) found that the development of the banking network of Greek and Italian banks in Albania favoured the growth of remittances of Albanian immigrants through the banking system. Karafolas (1995Karafolas ( , 1998 found that banks from Greece, Italy, Portugal and Spain created a banking network in countries where an immigrant population from those countries reside.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the availability of native banks in the host country and policies introduced by governments or corporates to channel remittances, such as foreign currency accounts and special exchange or interest rates, favour the use of banking services (Russell, 1986;Karafolas and Sariannidis, 2009;Siegel (forthcoming)). In addition to institutional factors, evidence suggests that the use of formal channels decreases in line with the differences between official exchange rates and black market rates (e.g.…”
Section: Characteristics Of and Reasons To Use Particular Remittance mentioning
confidence: 99%
“…Hernández-Coss (2005a) finds that transfer costs along the USA-Mexico corridor depend primarily on the volume of remittances for a country pair and the amount of competition in the market for international transfers. In particular, the growing presence of Greek and Italian banks in Albania has increased the Albanian migrants' use of formal transfer channels in Greece and Italy (Karafolas and Sariannidis 2009). In particular, the growing presence of Greek and Italian banks in Albania has increased the Albanian migrants' use of formal transfer channels in Greece and Italy (Karafolas and Sariannidis 2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Cooperation between or compatibility with the sending and receiving countries' financial sectors , the macroeconomic environment (for example dual exchange rates), political stability or instability and the strength or weakness of the banking system (Buencamino and Gorbunov 2002) also affect transfer costs. In particular, the growing presence of Greek and Italian banks in Albania has increased the Albanian migrants' use of formal transfer channels in Greece and Italy (Karafolas and Sariannidis 2009). Informal channels are often significantly cheaper than formal ones, particularly when informal transfers involve physical transport of cash and the sending and receiving country are geographically close Hernández-Coss et al 2008;Siegel et al 2009;Unger and Siegel 2006).…”
Section: Related Literaturementioning
confidence: 99%